The effectiveness of cooperative learning management using the TGT technique and Blooket applications towards problem-solving abilities of seventh grade students - Ariya Wongsaming; Wannatida Yonwilad; Noppakun Tongmual (Gemilang Maju Publikasi Ilmiah (GMPI), 2023)
This research aimed to investigate the effectiveness of cooperative learning management using the TGT technique and Blooket applications towards problem-solving abilities of seventh grade students. The study employed quasi-experimental design, with a pre-test and post-test control group. A cluster random sampling technique was used to select samples from each group of 35 seventh grade students. Research tools included learning management plans and quizzes to evaluate mathematical multiplication and exponential division skills and problem-solving abilitiest test. The t-test statistics was used for analysis. Results indicated that the problem-solving abilities of students who received mathematical learning activities on multiplication and exponential division through cooperative learning management of TGT techniques combined with blooket applications were significantly higher than those who received conventional teaching at .05 level of statistical significance.